2015
DOI: 10.1186/s12864-015-1552-y
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of Alu Y in the development of resistance to SN38 (Irinotecan) or oxaliplatin in colorectal cancer

Abstract: BackgroundIrinotecan (SN38) and oxaliplatin are chemotherapeutic agents used in the treatment of colorectal cancer. However, the frequent development of resistance to these drugs represents a considerable challenge in the clinic. Alus as retrotransposons comprise 11% of the human genome. Genomic toxicity induced by carcinogens or drugs can reactivate Alus by altering DNA methylation. Whether or not reactivation of Alus occurs in SN38 and oxaliplatin resistance remains unknown.ResultsWe applied reduced represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…These resistant cell lines were established by exposing chemotherapy-sensitive cells to gradually increasing concentrations of chemotherapy over a period of 8-10 months [25]. We thoroughly characterized these drug-resistant cell lines to identify important drug resistance mechanisms [25][26][27][28][29][30]. In accordance with several other studies with in vitro model systems [31], we found that BCRP overexpression was a key player of resistance to SN-38 [25].…”
Section: Introductionsupporting
confidence: 54%
“…These resistant cell lines were established by exposing chemotherapy-sensitive cells to gradually increasing concentrations of chemotherapy over a period of 8-10 months [25]. We thoroughly characterized these drug-resistant cell lines to identify important drug resistance mechanisms [25][26][27][28][29][30]. In accordance with several other studies with in vitro model systems [31], we found that BCRP overexpression was a key player of resistance to SN-38 [25].…”
Section: Introductionsupporting
confidence: 54%
“…So the insertion of full-length SVA (SINE-VNTR-Alu human retrotransposons) into intron 8 of the caspase 8 ( CASP8 ) gene is associated with cutaneous basal cell carcinoma and breast cancer [ 70 ]. To date, the most commonly used markers for human carcinogenesis are ALU repeats [ 71 73 ], which were shown to be significantly over-presented in breast cancer and colorectal cancer patients [ 48 , 49 , 74 , 75 ]. Repeatedly, it was shown that the development of various types of cancer is accompanied by an increase in the abundance of SINE and LINE elements in circulating exDNA [ 74 , 76 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from sperm samples, and bisulfite conversion was performed using the EZ DNA Methylation‐Gold Kit (Zymo Research; D5006). RRBS library construction and sequencing were performed at Genergy Bio (Shanghai, China) as described previously .…”
Section: Methodsmentioning
confidence: 99%